PENGGUNAAN LABORATORIUM VIRTUAL PHET SIMULATION SEBAGAI SOLUSI PRAKTIKUM WAKTU PARUH - Rahel Rehuella Marpaung; Nabeela Rahma Noor Aziz; Mia Dewi Purwanti; Putri Nabila Sasti; Dandan Luhur Saraswati (Journal of Teaching and Learning Physics, 2021)
Covid-19 has affected the education sector in Indonesia. The purpose of this study was to determine the decay rate of Carbon-14 and Uranium-238 isotopes in the first half, second and third half, and to determine the level of accuracy of the experiment using PhET Simulation. The method used in this research is the experimental method. The results showed the percentage of decay rate of Carbon-14 in the first half was 49%, the second half-life was 75.4%, and the third half-life was 84.5%. While the percentage of Uranium-238's decay rate in the first half is 49.6%, the second half-life is 74%, and the third half-life is 85.9%. The accuracy level for the Carbon-14 isotope using PhET Simulation was 98.35%, while the accuracy level for Uranium-238 isotope using PhET Simulation was 99.95%. Therefore, PhET Simulation can be used as a solution for part-time practicum during the Covid-19 period.